VIRTUAL COLLABORATIVE WORK IN THE PRODUCTION OF ARGUMENTAL TEXTS IN SECONDARY FOURTH STUDENTS IN TIME OF COVID-19 - Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The present research was developed with the objective of determining how virtual collaborative work influences the production of argumentative texts in secondary school students of a public institution in COVID-19 time. It was of the applied type of quantitative approach with quasi-experimental design following the guidelines of the four groups of Solomon: Two experimental groups (classroom A and classroom C) and two control groups (classroom B and classroom D) in which 100 students participated who were evaluated with a rubric of argumentative text production. The instrument had three dimensions: Superstructure, macrostrutura and microstructure. A set of activities related to the production of argumentative texts through virtual collaborative work was carried out in each of the program sessions in which the pilot groups participated. The results of the research suggest that virtual collaborative work allows the achievement of the production of argumentative texts.In this sense, it is important that teachers are trained in the management of virtual collaborative tools so that they work with the students successfully proposed activities.